(untitled) (Comprehensive Journal of Science, 2026)
The phenomenon of low academic achievement is considered one of the most significant educational and social problems facing students in schools, due to its negative impact on both individuals and society. This decline is attributed to a set of interrelated factors, including family, psychological, educational, and economic factors. The present study focuses on the role of the social worker in reducing the phenomenon of low academic achievement, emphasizing the importance of cooperation with subject teachers to achieve effective intervention. The study also highlights the necessity of an integrated role between the social worker and teachers, which contributes to: The early identification of low-achieving students. Addressing social and psychological problems. Providing guidance and developmental support for students. Enhancing cooperation between the school and the family. Furthermore, the study indicates that the continuous development and training of both social workers and teachers in modern teaching methods contribute to improving academic achievement, whereas the lack of cooperation among the concerned parties leads to the persistence of the problem.